Gender-Responsive Probation During the COVID-19 Pandemic: Learning from Justice-Involved Women and Their Supervising Officers - Belisle, Linsey A. (Victims & offenders, 2023)
In the Spring of 2020, the COVID19 pandemic forced community corrections agencies to adapt their day-to-day processes for supervising individuals and maintaining public safety. These forced adaptations allowed the authors to explore how these changes (i.e., tele-supervision) impacted women and those who supervised them at a probation agency in a large metropolitan county in a Western U.S. state. To date, limited research surrounds how COVID-related adaptations impacted gender-responsive, or women-centered, community supervision caseloads. To address this gap in the literature, the current study utilizes a qualitative approach to explore the experiences of 17 community corrections staff and clients on gender-responsive probation supervision during the pandemic. Their narratives suggest both positive outcomes (e.g., accessibility, reducing tendencies to over-supervise) and challenges (e.g., accountability, lacking a relational component) with tele-supervision and tele-treatment models. It is critical to utilize the lived experiences of those directly impacted by COVID-related changes, including community corrections staff and clients, to help shape gender-responsive supervision moving forward.